Employee perceptions of organisational legitimacy as impersonal bases of organisational trustworthiness and trust. Issue 2 (3rd July 2017) - Lamertz, Kai; Bhave, Devasheesh P.
ABSTRACT: Prior research has amply demonstrated that employees' personal relationship with the organisation influences their trust in it. In this two-study investigation, we examine how employees' beliefs about the organisation's legitimacy relate to their organisational trust because legitimacy signals organisational trustworthiness in the impersonal system of the institutional environment. Results from Study 1, which drew on data from one organisation, reveal that employees' legitimacy beliefs are related to their organisational trust. Furthermore, results from Study 2, which are based on data from five organisations, reveal that employees' judgment of the organisation's trustworthiness mediates the relationship between legitimacy beliefs and organisational trust. Overall, our findings create a new avenue for trust research by advancing the idea that employees' trust in their employer organisation derives in part from the reflection of trustworthiness that arises due to the organisation's association with the institutional environment.